DISCONNECTIONS AND DEPTHS: ALIENATION AND THE UNCONSCIOUS IN TORU DUTT’S POETRY, A FREUDIAN PERSPECTIVE - Bhardwaj, Rahul; Reshi, Javid Ahmed (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This research paper employs Sigmund Freud’s Iceberg principle and theory of Alienation to investigate the unconscious meanings and symbolism in Torulata Dutt’s poems, “The Lotus," "The Ballad of Savitri," and "Our Casuarina Tree". The poems are treated as the bottom of an iceberg, containing repressed thoughts, reminiscences and desires, demonstrating a flux between conscious and unconscious thoughts. The paper also explores the themes of alienation, revealing how the poet portrays the consequences of alienation on the human experience, including the disengagement from oneself, others, and the physical world. It aims at providing a deeper understanding of the poems by delving deep under the surface layers to enable readers to cherish the richness and complexity of Toru’s poetry. Dutt’s poetry represents her struggles with identity, culture, and loneliness, offering a refined exploration of alienation in its various forms. Her works explore the complexities of cultural uprootedness, spiritual starvation, and isolation, crafting a unique poetic voice that resonates with readers across cultures. The selected poems, taken from her collections Ancient Ballads and Legends of Hindustan (1877) and A Sheaf Gleaned in French Fields (1876), showcase Dutt’s ability to convert personal experiences of isolation into universal explorations of the human psyche. This intervention seeks to provide a deeper understanding and nuanced appreciation of her literary oeuvre.